Antimetastatic activity of novel ruthenium (III) pyridine complexes. (7th September 2016) - Gu, Liwei; Li, Xiaodong; Ran, Qingsen; Kang, Chen; Lee, Canghai; Shen, Jianying
Abstract: Ruthenium‐based complexes have emerged as promising anticancer, especially antimetastatic agents. Among them, NAMI‐A ( trans ‐[Ru(III)Cl4 (DMSO)(Im)][ImH], Im = imidazole, DMSO = dimethyl sulfoxide) was well studied. In this study, we studied the antimetastatic activities of two novel NAMI‐A derivatives containing pyridine, G26b and G94a, using cultured cells and tumor‐bearing mice. Same to NAMI‐A, these two complexes displayed little direct cytotoxicity to the cancer cells in vitro and in vivo, but they, especially G26b, significantly reduced the occurrence and development of lung metastases in mice bearing the 4T1 mammary carcinoma. In vitro, these two complexes displayed significant suppressive effect on invasion and migration of cells and tube formation of human umbilical vein endothelial cell, to the same extent of NAMI‐A. The transcription of important molecules involved in metastasis, matrix metalloproteinase 2 and 9 (MMP‐2 and ‐9), and vascular endothelial growth factor, was suppressed by the two complexes, as well as NAMI‐A. Plasma atomic emission spectrometer showed G26b had a longer Ru‐elimination time in lung, which may be a reason for better antimetastatic effect of G26b than NAMI‐A. Our results have demonstrated that G26b is a more effective antimetastatic agent than NAMI‐A. Abstract : The ruthenium (III)‐pyridine complexes, G26b and G94a, which is derived from NAMI‐A, could strongly reduce the occurrence and development of lung metastases in mice when kept a slower Ru elimination, which prolonged contact with the metastatic cells in the lungs. The ruthenium (III)‐pyridine complexes had coped better than well‐studied NAMI‐A.